2013
DOI: 10.1371/journal.pntd.0002549
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Diversity in the Trypanosoma congolense Trans-sialidase Family

Abstract: Trans-sialidases are key enzymes in the life cycle of African trypanosomes in both, mammalian host and insect vector and have been associated with the disease trypanosomiasis, namely sleeping sickness and nagana. Besides the previously reported TconTS1, we have identified three additional active trans-sialidases, TconTS2, TconTS3 and TconTS4, and three trans-sialidase like genes in Trypanosoma congolense. At least TconTS1, TconTS2 and TconTS4 are found in the bloodstream of infected animals. We have characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(61 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…The enzymatic activities of TconTSs were previously characterised [ 30 , 31 ] using recombinant proteins expressed in CHO-Lec1 cells that therefore contain N -glycans of the high-mannose-type, similar to the recombinant huS2-Fc used here in binding/inhibition assays. N -glycosylation site prediction analysis revealed 8–9 potential sites in TconTSs, and none for the attached SNAP-tag ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enzymatic activities of TconTSs were previously characterised [ 30 , 31 ] using recombinant proteins expressed in CHO-Lec1 cells that therefore contain N -glycans of the high-mannose-type, similar to the recombinant huS2-Fc used here in binding/inhibition assays. N -glycosylation site prediction analysis revealed 8–9 potential sites in TconTSs, and none for the attached SNAP-tag ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to TcTS, only a few studies have investigated the enzymatic activities of T . brucei TS (TbTS) [ 26 29 ] and TconTS [ 6 , 30 , 31 ]. However, given the overall high primary sequence similarity of all TS at the catalytic site it can be assumed that the molecular mechanisms of the African TS are similar to those described for TcTS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The members of this enzyme class use host glycoconjugates as sialyl donors, but transfer the SA to parasite acceptor molecules rather than water. Coinciding with their highly conserved sialidase-like active site, it has been shown that trans-sialidases exhibit residual sialidase activity in the absence of the appropriate acceptor (Cross & Takle, 1993;Harrison et al, 2001;Gbem et al, 2013). In contrast to sialidases, it is interesting to note that the structural and mechanistic features of trans-sialidases remain understudied, as only a handful of these enzymes have been characterized (Cheng et al, 2008(Cheng et al, , 2009Gut et al, 2008;Newstead et al, 2004).…”
Section: Introductionmentioning
confidence: 99%